50 years of asthma: UK trends from 1955 to 2004. Issue 1 (22nd December 2006) - Ross Anderson, H; Gupta, Ramyani; Strachan, David P; Limb, Elizabeth S
Abstract : Trends in asthma indicators from population surveys (prevalence) and routine statistics (primary care, prescriptions, hospital admissions and mortality) in the UK were reviewed from 1955 to 2004. The prevalence of asthma increased in children by 2 to 3-fold, but may have flattened or even fallen recently. Current trends in adult prevalence are flat. The prevalence of a life-time diagnosis of asthma increased in all age groups. The incidence of new asthma episodes presenting to general practitioners increased in all ages to a plateau in the mid 1990s and has declined since. During the 1990s, the annual prevalence of new cases of asthma and of treated asthma in general practice showed no major change. Hospital admissions increased from the early 1960s, more so in children, until the late 1980s and have fallen since. Asthma mortality showed two waves, a shorter and more intense one in the mid 1960s and a longer and less intense one in the late 1970s and early 1980s. The relative roles of diagnostic transfer, coding changes, medical care and epidemiological factors are discussed.